Mobile Phone Technology and Reading Behaviour: Commentary on the FunDza Programme - Johann Louw; Joha Louw-Potgieter (The African Journal of Information and Communication, 2015)
South African learners generally perform badly on external tests of reading literacy. In the 2011 international Progress in International Reading Literacy Study (PIRLS), South African Grade 4 learners performed poorly in comparison with their international counterparts, especially on higher order comprehension (Howie, van Staden, Tshele, Dowse, & Zimmerman, 2012). The 2013 Annual National Assessments reported a national average percentage of 43% for Grade 9 learners in their home language and 35% in a first additional language, which often is English (Department of Basic Education, 2013). The Department’s report recommended that learners be encouraged to read additional books, and more widely, to improve their scholastic attainment. There is much evidence to support the argument that reading for pleasure has a positive effect on both personal and educational development (e.g. Clark, 2011). Encouraging learners to engage in self-initiated reading as a leisure activity therefore may be positively related to reading literacy. Unfortunately, many South African learners attend schools with no libraries, and come from households without resources, including books, to promote reading (Howie et al., 2012). The question then is how to fill this gap, to provide reading content to young people who are interested in reading,but who find it difficult to access reading material that would interest them. For a number of years now, mobile phone technology has been seen increasingly as a promising platform to deliver educational services, including literacy development (Lee & Wu, 2012). UNESCO, for example, organises mobile learning weeks. At the second such week,it specifically addressed the question of mobile technology and literacy development for young people and adults(UNESCO, 2013). In South Africa at least two non-profit organisations have developed projects to deliver reading materials to young people via this medium. One is the m4Lit project, funded by the Shuttleworth Foundation, which gives young readers access to novels via the mobile phone. Vosloo (2010) found that these novels attracted over 60,000 reads, suggesting that mobile phone-based reading is a viable strategy to encourage reading. Our researchers have been working with the second organisation, the FunDza Literacy Trust, to provide an assessment of the viability of mobile phones to attract readers. The Trust has been in existence since 2011 and provides readers with locally-written material in a number of South African languages through the mobile social application Mxit or FunDza’s website, http://www.FunDza.co.za This research note offers an overview of work on FunDza reported in three, separate, scholarly publications.